Ovarian hormones, menstrual cycle phase, and smoking: a review with recommendations for future studies - Wetherill, Reagan R. (Curr Addict Rep, 2016)
Cigarette smoking continues to be the leading cause of preventable morbidity and mortality. Similar to other addictive substances, the prevalence of cigarette smoking is greater among men than women, yet women are less successful at quitting smoking. Preclinical and clinical research suggests that ovarian hormones (i.e., estradiol and progesterone), which fluctuate over the course of the menstrual cycle, may contribute to these sex differences. Specifically, research suggests that progesterone may protect against cigarette smoking and nicotine addiction; whereas estradiol may underlie enhanced vulnerability. In this review, we discuss new research on ovarian hormone and menstrual cycle phase effects on smoking-related responses and behavior in women, including studies examining neural responses to smoking cues, hormonal influences on medication-assisted smoking cessation, and acute smoking abstinence. We highlight innovative studies with strong research methodology and provide suggestions for future research that may allow evidence-based knowledge for immediate translation to the clinic to guide novel, hormonally-informed treatment strategies. Thus, rigorous scientific study holds the potential to reduce relapse rates, thus improving the health and saving the lives of the many thousands of women who unfortunately do not respond to current treatments.